Happy Anniversary to the Journal of Dental Hygiene! - Wilder, Rebecca S. (Journal of Dental Hygiene, 2026)
This article focuses on the upcoming 100th anniversary of the Journal of Dental Hygiene (JDH) in 2026, highlighting its historical development and evolving role in the dental hygiene profession. Established in 1927 by the American Dental Hygienists’ Association (ADHA), the JDH began as a primary communication tool for dental hygienists and has since transformed into a peer-reviewed research publication supporting the National Dental Hygiene Research Agenda. The journal has adapted to changes in the profession and publishing landscape, including shifts in research focus, the transition to digital formats, and indexing in major biomedical databases. Looking forward, the JDH plans to continue advancing dental hygiene knowledge through innovative features and by addressing critical issues in the field.